2018
DOI: 10.1186/s12885-017-3896-y
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of p38 MAPK activity leads to cell type-specific effects on the molecular circadian clock and time-dependent reduction of glioma cell invasiveness

Abstract: BackgroundThe circadian clock is the basis for biological time keeping in eukaryotic organisms. The clock mechanism relies on biochemical signaling pathways to detect environmental stimuli and to regulate the expression of clock-controlled genes throughout the body. MAPK signaling pathways function in both circadian input and output pathways in mammals depending on the tissue; however, little is known about the role of p38 MAPK, an established tumor suppressor, in the mammalian circadian system. Increased expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…The p38–MAPK signaling pathway has been implicated in the inflammatory response, cell cycle regulation, cell death, differentiation, and tumor progression. 36 Goldsmith et al 37 reported that inhibition of the p38–MAPK pathway led to decreased glioma cell invasion. Another study found that miR-3188 promoted cell proliferation and migration via the p38–MAPK pathway in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The p38–MAPK signaling pathway has been implicated in the inflammatory response, cell cycle regulation, cell death, differentiation, and tumor progression. 36 Goldsmith et al 37 reported that inhibition of the p38–MAPK pathway led to decreased glioma cell invasion. Another study found that miR-3188 promoted cell proliferation and migration via the p38–MAPK pathway in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike normal HA glial cells, phosphorylated p38 MAPK levels were high and arrhythmic in invasive IM3 glioma cells. Despite this arrhythmicity in p38 MAPK phosphorylation, timed application of p38 MAPK activity inhibitor VX-745 to IM3 cells at timepoints corresponding to low activity ofP38 MAPK in HA glial cells reduced the invasive properties of IM3 cells (90).…”
Section: The Clock Relation To Angiogenesis and Invasiveness Of Gliomamentioning
confidence: 99%
“…The authors proposed that MK2 could have a role in AD brain pathology. Because many p38α inhibitors were not successful in clinical development due to their toxicological profiles inducing apoptosis [ 62 , 63 , 64 ], recent experimental attempts were initiated to find new MK2 inhibitors that could serve as anti-inflammatory agents [ 65 ]. For example, an in vitro study revealed that MK2 inhibitors could be superior to p38 inhibitors because these latter inhibitors induce increased phosphorylated C-Jun kinase (pJNK) and caspase 3 activations (leading to possible increased cellular apoptosis) as compared to MK2 inhibitors [ 66 ].…”
Section: Mk2 and Admentioning
confidence: 99%